Tecnologías digitales y su impacto en las actividades laborales de las secretarías en el Colegio de Bachillerato Ponce Enríquez - Lapo Tapia, Johanna Stefania (2022)
The main purpose of this case study was based on research on digital technologies and their impact on the work activities of the secretaries of the Ponce Enriquez High School, within which we tried to determine the degree of importance they give to these technologies to carry out their activities and fulfill their functions and responsibilities within the institution. Technological evolution has been described as the process by which tools such as computers and the Internet have replaced and improved the forms of communication between people, a process that has progressed impressively and has been especially useful in the work performed by the secretaries, for that reason, the objective of the study was to determine how and to what extent digital technologies impact the secretarial activities of the institution under study. In addition, the research allowed to know different concepts of several authors, on both variables, which gave ample information to achieve a complete study of the topic addressed. The descriptive type of research was also used, which provided details on both variables, and the method of analysis, in order to understand important data on the phenomena presented in the project. The survey was used, with a questionnaire of 10 questions, to know the opinion of the collaborators in this institution, whose results were tabulated to obtain the results and establish the most suitable solutions to the problem. Finally, both variables were linked and it was concluded that it is necessary to train these secretaries in order to improve their performance and fulfill their work activities more effectively.